2020
DOI: 10.1128/aem.01194-20
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Effects of Crude Oil and Corexit 9500 on Their Biodegradation in Arctic Seawater

Abstract: The risk of petroleum spills coupled with the potential application of chemical dispersants as a spill response strategy necessitates further understanding of the fate of oil and dispersants and their interactive effects during biodegradation. Using Arctic seawater mesocosms amended with either crude oil, Corexit 9500, or both together, we quantified the chemical losses of crude oil and Corexit 9500 and identified microbial taxa implicated in their biodegradation based on shifts in the microbial community stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…Recent incubation studies have also demonstrated an upregulation of β-oxidation gene transcripts in treatments that contained Corexit compared to oil-only treatments and unamended controls (Doyle et al, 2020;Peña-Montenegro et al, 2020).Based on the significant enrichment of fadE, fadA, and fadB genes at the 5-day time point, increased β-oxidation of chemical compounds was likely occurring in the presence of Corexit and oil + Corexit relative to oil-only or the control. This agrees with previously reported chemical loss data from this experiment, which showed that the majority of Corexit surfactant loss occurred within 5 days and the majority of oil loss within 10 days (Figure 3; Gofstein et al, 2020). When examining the constituents of Corexit 9500 compared to crude oil, their chemical structures, which contain multiple ester groups, (Figure 5A) have functional groups that may lead to their being more labile than the alkanes present in crude oil due to fewer steps being required to prepare esters to undergo β-oxidation (Figure 5B).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Recent incubation studies have also demonstrated an upregulation of β-oxidation gene transcripts in treatments that contained Corexit compared to oil-only treatments and unamended controls (Doyle et al, 2020;Peña-Montenegro et al, 2020).Based on the significant enrichment of fadE, fadA, and fadB genes at the 5-day time point, increased β-oxidation of chemical compounds was likely occurring in the presence of Corexit and oil + Corexit relative to oil-only or the control. This agrees with previously reported chemical loss data from this experiment, which showed that the majority of Corexit surfactant loss occurred within 5 days and the majority of oil loss within 10 days (Figure 3; Gofstein et al, 2020). When examining the constituents of Corexit 9500 compared to crude oil, their chemical structures, which contain multiple ester groups, (Figure 5A) have functional groups that may lead to their being more labile than the alkanes present in crude oil due to fewer steps being required to prepare esters to undergo β-oxidation (Figure 5B).…”
Section: Discussionsupporting
confidence: 93%
“…The taxa previously reported to proliferate in response to oil and/or Corexit in this incubation study (Gofstein et al, 2020) were associated with enriched gene transcripts for several key metabolic and biogeochemical processes relevant to contaminant degradation including fatty acid degradation, nitrogen cycling, and sulphur cycling (Table 1). Based on the taxonomic affiliations of the metabolic transcripts, different populations became metabolically active in response to oil and/or Corexit (Figure 4).…”
Section: Taxonomic Affiliation Of Transcriptsmentioning
confidence: 85%
See 1 more Smart Citation
“…Their results showed a quick initial removal of hydrocarbons by volatilization, but microbial biodegradation of crude oil was low, especially at the lower temperature. McFarlin et al (2018) [157] and Gofstein et al (2020) [154] quantified biodegradation and abiotic losses of ANS crude oil and Corexit 9500 in Arctic seawater mesocosms. They identified microorganisms potentially involved in biodegradation of these substrates using tools based on gene analysis.…”
Section: Fate and Weathering Studiesmentioning
confidence: 99%
“…Toxicity experiments performed on a closely related species indicated that oil had little effect on coral's health but that oil and dispersant mixtures were particularly toxic to corals (DeLeo et al, 2016;Goodbody-Gringley et al, 2013;Negri et al, 2018). The long-term persistence of elevated DOSS concentrations on beaches and in the deep sea demonstrates that at least some of the components of dispersants are persistent in the environment (Gofstein et al, 2020;Gray et al, 2014;Mascarelli, 2011).…”
Section: 44mentioning
confidence: 99%